Pendidikan untuk Pemerataan Pembangunan: Memperjuangkan Hak Semua Anak - Ismatul Maula; Irwandi Irwandi; Avid Leonardo Sari; Dorce Sisfiani Sarimin; Rolly H. S. Rondonuwu (Departement of Mathematics Education, 2023)
This study aims to explore the role of education in realizing equitable development by fighting for all rights. This study was conducted through a qualitative approach with descriptive methods. The results of the study show that education plays an important role in encouraging equitable development through providing fair and equitable access to education, empowering communities through education, and improving the quality of education. However, there are still challenges in realizing equitable development through education, such as a lack of education funding and infrastructure and a lack of community participation in the development process. Therefore, this study recommends that the government and related institutions make efforts to fight for all rights to education, improve the quality of education, and encourage community participation in the development process.